2006
DOI: 10.1128/aem.02923-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Macrofoam Swab Protocol for the Recovery of Bacillus anthracis Spores from a Steel Surface

Abstract: A protocol to recover Bacillus anthracis spores from a steel surface using macrofoam swabs was evaluated for its accuracy, precision, reproducibility, and limit of detection. Macrofoam swabs recovered 31.7 to 49.1% of spores from 10-cm 2 steel surfaces with a <32.7% coefficient of variation in sampling precision and reproducibility for inocula of >38 spores.Thousands of swab samples of Bacillus anthracis spores were taken during investigations of the 2001 bioterrorist events (3,7,10,11,12,13), but no validated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
101
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(113 citation statements)
references
References 10 publications
5
101
7
Order By: Relevance
“…These findings were consistent with those in our previous report, which demonstrated that the use of the SETS was optimal for detection of Francisella tularensis from spiked swabs (39). There are established protocols for recovery of B. anthracis spores from environmental swabs (13,14); however, this is the first report to evaluate procedures and develop a protocol for recovery of B. anthracis vegetative cells from clinical swabs. Further, this protocol was successfully employed for the identification of B. anthracis from cutaneous anthrax outbreak specimens.…”
Section: Discussionsupporting
confidence: 82%
“…These findings were consistent with those in our previous report, which demonstrated that the use of the SETS was optimal for detection of Francisella tularensis from spiked swabs (39). There are established protocols for recovery of B. anthracis spores from environmental swabs (13,14); however, this is the first report to evaluate procedures and develop a protocol for recovery of B. anthracis vegetative cells from clinical swabs. Further, this protocol was successfully employed for the identification of B. anthracis from cutaneous anthrax outbreak specimens.…”
Section: Discussionsupporting
confidence: 82%
“…Macrofoam swabs were demonstrated to collect 30῎ more spores 8), 22) even at spore concentrations ῌ10 1 spores per preparation 8) . Recovery e$ciencies ῍90῎ were achieved from macrofoam swabs during direct inoculation studies (recovery e$-ciency from rayon and polyester was decidedly lower 22) ).…”
Section: Surface Samplingmentioning
confidence: 99%
“…Further, because of the variability produced by having to deal with live organisms, it is not likely that the accuracy in measurement for spores will meet the NIOSH criteria. In studies of spore recovery from surfaces, the variability of CFUs per sample is not usually reported, only the recovery efficiency and its variability (Rose et al 2004;Hodges et al 2006;Brown et al 2007a;2007b;2007c). Recovery efficiency values reported in the Brown et al studies had a range of 28-90%; .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have primarily investigated sampling techniques by inoculating surfaces using a high-concentration liquid suspension of bacteria or spores (Rose et al 2004;Hodges et al 2006) or by evaluating environmental samples (Krischner and Puleo 1979;Sanderson et al 2004). These approaches either do not directly simulate the dry deposition of bacteria or spores from the aerosol state or may not have sufficient precision or accuracy to adequately differentiate between techniques.…”
Section: Introductionmentioning
confidence: 99%